Local Immune Control of Latent Herpes Simplex Virus Type 1 in Ganglia of Mice and Man - St. Leger, Anthony J.; Koelle, David M.; Kinchington, Paul R.; Verjans, Georges Michel G. M. (Frontiers in Immunology, 2021)
Herpes simplex virus type 1 (HSV-1) is a prevalent human pathogen. HSV-1 genomes persist in trigeminal ganglia neuronal nuclei as chromatinized episomes, while epithelial cells are typically killed by lytic infection. Fluctuations in anti-viral responses, broadly defined, may underlay periodic reactivations. The broad ganglionic immune response to HSV-1 infection includes cell-intrinsic responses in neurons, innate sensing by several cell types, and the infiltration and persistence of antigen-specific T-cells. The mechanisms specifying the contrasting fates of HSV-1 in neurons and epithelial cells may include differential genome silencing and chromatinization, dictated by variation in access of immune modulating viral tegument proteins to the cell body, and protection of neurons by autophagy. Innate responses have the capacity of recruiting additional immune cells and paracrine activity on parenchymal cells, for example via chemokines and type I interferons. In both mice and humans, HSV-1-specific CD8 and CD4 T-cells are recruited to ganglia, with mechanistic studies suggesting active roles in immune surveillance and control of reactivation. In this review we focus mainly on HSV-1 and the TG, comparing and contrasting where possible observational, interventional, and in vitro studies between humans and animal hosts.